Implementasi Peraturan Pemerintah No. 45 Tahun 1990 Tentang Surat Izin Perceraian Bagi Pegawai Negeri Sipil (PNS) di Pengadilan Agama Maros Kelas 1B - Rahmatullah, Andi Muhammad Ridha; Sofyan, Sofyan; Azizah, Nur (Universitas Islam Negeri Alauddin Makassar, 2023)
Divorce can be done by anyone who has been married including Civil Servants. The main point of this research is the Implementation of Government Regulation No. 45 of 1990 concerning Divorce Permits for Civil Servants (PNS) in Maros Class 1B Religious Court. This study aims to determine the extent of implementation/application of Government Regulation Number 45 of 1990 concerning divorce licenses for civil servants in the Maros Religious Court. The type of research used is Qualitative Field Research with descriptive methods and sociological approaches. The results showed that the Maros Religious Court class IB has implemented the mandate of Government Regulation number 45 of 1990 concerning divorce permits for civil servants in the Maros Religious Court class IB in terms of providing services. Because every civil servant who wants to carry out a divorce first gets permission from the superior.